2022
DOI: 10.3389/fimmu.2022.874769
|View full text |Cite
|
Sign up to set email alerts
|

The NOD Mouse Beyond Autoimmune Diabetes

Abstract: Autoimmune diabetes arises spontaneously in Non-Obese Diabetic (NOD) mice, and the pathophysiology of this disease shares many similarities with human type 1 diabetes. Since its generation in 1980, the NOD mouse, derived from the Cataract Shinogi strain, has represented the gold standard of spontaneous disease models, allowing to investigate autoimmune diabetes disease progression and susceptibility traits, as well as to test a wide array of potential treatments and therapies. Beyond autoimmune diabetes, NOD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 211 publications
0
20
0
1
Order By: Relevance
“…In this study, we identified B cell-specific phenotypes in the thymic APC pool of NOD mice, a common mouse model for autoimmune diabetes and other autoimmune syndromes. 16 , 17 , 46 In addition to a B cell-specific deficit of co-stimulation, NOD thymic B cells do not switch to secondary isotypes as efficiently as in other mouse strains, a trait that correlates with a reduction of CD4SP thymocyte tolerance to self-antigens. To investigate the potential impact of isotype switching by thymic B cells on T-cell tolerance and autoimmunity, we generated NOD.AID −/− mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified B cell-specific phenotypes in the thymic APC pool of NOD mice, a common mouse model for autoimmune diabetes and other autoimmune syndromes. 16 , 17 , 46 In addition to a B cell-specific deficit of co-stimulation, NOD thymic B cells do not switch to secondary isotypes as efficiently as in other mouse strains, a trait that correlates with a reduction of CD4SP thymocyte tolerance to self-antigens. To investigate the potential impact of isotype switching by thymic B cells on T-cell tolerance and autoimmunity, we generated NOD.AID −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes (T1D) is an autoimmune disease characterized by the destruction of insulin-producing pancreatic β cells. 15 The non-obese diabetic (NOD) mouse strain is autoimmune-prone 16 and spontaneously develops autoimmune diabetes. 17 , 18 , 19 T cells are necessary and sufficient for autoimmune diabetes onset and progression, 20 , 21 , 22 and it has been suggested that defects in central T-cell tolerance in NOD mice contribute to the development of autoimmune diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The NOD mouse is best known as a model of spontaneous T1D; however, they develop multiple other spontaneous autoimmune conditions such as thyroiditis and Sjögren’s syndrome. Immunogenetic components contributory to NOD autoimmune disease include the TCR-MHC interaction (signal 1), co-stimulatory molecules (signal 2), and cytokines (signal 3) as reviewed by Aubin et al (Aubin et al 2022 ). The NOD immunogenetic background is susceptible to autoimmunity and to understand the basis of this heightened immunity, congenic mapping experiments were conducted to identify genetic regions responsible for the diabetes phenotype.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Second, they may impair general tolerance mechanisms (as suggested by the occurrence of other autoimmune conditions in both T1D patients 2 and its animal model, the non-obese diabetic (NOD) mouse. 3 Administration of exogenous insulin for the last 100 years has saved countless lives; however, it can rarely achieve tight regulation of blood glucose levels, such that episodes of hyper- and hypoglycemia remain commonplace, and their recurrence leads to long-term complications. 4 Even when perfect glycemic control is achieved, there is still a residual 2- to 3-fold hazard ratio of death from any cause, particularly from cardiovascular disease, in T1D vs. non-diabetic individuals.…”
Section: Type 1 Diabetes and The Need For Antigen-specific Therapiesmentioning
confidence: 99%